#TITLE_ALTERNATIVE# - SATIAWAN (NIM 124 04 021), SONI
Total magnetic intensity (TMI) is the superposition of regional anomaly and residual (local) anomaly. Regional anomaly is associated with general geological condition that dominant at research area and usually identified with low frequency anomaly. In the other hand, local anomaly usually is high frequency and contains information of shallow anomaly source. This research applied upward continuation and wavelength filter to synthetic geomagnetic data. The Use of upward continuation to certain altitude and wavelength filter is intended to produce appropriate regional and local anomalies. The methods were tested on synthetic models consisting of deep anomaly and shallow anomaly at 500 m and 200 m respectively. Upward continuation to altitude 200 m and 300 m results low frequency anomaly associated with regional anomaly. Separation of regional-residual using wavelength filter results in local anomaly similar to shallow source anomaly. It has been found that depth-wavelength relationship is h = 1,5 h.